Cover. (27th September 2017) - Joshi, Shivali S.; Wong, Daniel; Castillo, Eliana; Swain, Mark G.; Coffin, Carla S.
Abstract : Front cover : The cover image, by Shivali S. Joshi et al., is based on the Original Article Peripartum cytokine flares in a multiethnic cohort of chronic hepatitis B carriers does not correlate with hepatitis B virus suppression or increased risk of liver disease, DOI:10.1111/aji.12707 .